2012
DOI: 10.1371/journal.pone.0049335
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Increased Stress Tolerance of Saccharomyces cerevisiae Encapsulated in Liquid Core Alginate-Chitosan Capsules

Abstract: Saccharomyces cerevisiae CBS8066 encapsulated in semi-permeable alginate or alginate-chitosan liquid core capsules have been shown to have an enhanced tolerance towards complex dilute-acid lignocellulose hydrolysates and the lignocellulose-derived inhibitor furfural, as well as towards high temperatures. The underlying molecular reasons for these effects have however not been elucidated. In this study we have investigated the response of the encapsulation on the proteome level in the yeast cells, in comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 45 publications
3
30
1
Order By: Relevance
“…The reason for this is unknown and the effect was not observed in the other media. A decreased yield has been reported for encapsulated yeast, where the cells are also packed tightly together, why the reason for the increased yield in the current case remains elusive (17). The glycerol yields were significantly lower in the two furfural-containing media.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…The reason for this is unknown and the effect was not observed in the other media. A decreased yield has been reported for encapsulated yeast, where the cells are also packed tightly together, why the reason for the increased yield in the current case remains elusive (17). The glycerol yields were significantly lower in the two furfural-containing media.…”
Section: Resultsmentioning
confidence: 54%
“…By computer simulations, it has been shown that diffusion limitations in the encapsulated cell pellet lead to concentration gradients of both nutrients and convertible inhibitors (19). It has also been shown that encapsulation of yeast induces a starvation stress response which increases the robustness of the yeast community (11,17). The fact that the cells grow rather slowly inside the capsules might also aid in increasing the robustness, since slow-growing cells have been shown to have increased stress tolerance (48).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of TMT proteomics to study microbial communities Prior proteomics studies using TMT-or isobaric tags for relative and absolute quantification-based isobaric chemical labeling have been applied exclusively to human tissues, plants and cultured isolates (for example, Dayon et al, 2010;Lee et al, 2011;Li et al, 2012;Westman et al, 2012;Chen et al, 2013;Paulo et al, 2013;Li et al, 2014). Here, we validate the TMT-based quantitative proteomics approach as applied to microbial communities, showing precise quantification of thousands of proteins across a large range of fold changes.…”
Section: Discussionmentioning
confidence: 68%
“…In order to overcome the problem, the mixture solution of cell suspension and cation ions is modified by addition of thickener to increase its viscosity such as sucrose (Zhang and Salsac 2012;Nussinovitch et al 1996Nussinovitch et al , 1997, dextran (Zhang and Salsac 2012;Nigam et al 1988), starch (Goderska et al 2003;Dembczynski and Jankowski 2002;Jankowshi et al 1997), xanthan gum (Koyama and Seki 2004a;Seong et al 1997;Yoo et al 1996;Chang et al 1996;Cheong et al 1993), guar gum (Nussinovitch et al 1996), polyethylene glycol (PEG) (Koyama and Seki 2004a), hydroxypropylmethylcellulose (Torre et al 2000), chitosan (Mi et al 2002) and carboxylmethylcellulose (CMC) (Westman et al 2012;Youngsukkasem et al 2012;Ylitervo et al 2011;Ji et al 2007;Yan and Lehe 2007;Talebnia et al 2005;Chai et al 2004;Blandino et al 2000Blandino et al , 2001Blandino et al , 2002Patel et al 2000;Blandino et al 1999;Nussinovitch et al 1996). In some application, the viscous liquid inner core of the capsule may interrupt the functionality of the encapsulated biocatalyst.…”
Section: Extrusion-dripping (Liquid Droplet Forming) Methodsmentioning
confidence: 99%